2020
DOI: 10.5582/ddt.2020.01010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed long non-coding RNAs associated with dilated cardiomyopathy using integrated bioinformatics approaches

Abstract: long Non-coding RNAs, biomarker, dilated cardiomyopathy, bioinformatics analysis The aim of this study was to identify novel long non-coding RNA (lncRNA) biomarkers associated with dilated cardiomyopathy (DCM) and reveal the potential molecular mechanisms of DCM development using bioinformatics approaches. The array data of GSE5406, including 108 DCM samples and 16 non-failing control samples, were obtained from the Gene Expression Omnibus database. The differentially expressed lncRNAs were identified using li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…Si (2023) has screened the associated genes and biological pathways of inflammatory dilated cardiomyopathy (DCMi) [ 50 ]. Luo et al (2020) identified novel long non-coding RNA (lncRNA) biomarkers associated with DCM and revealed the potential molecular mechanisms of DCM development using bioinformatics approaches (dataset GSE5406 from GEO) [ 51 ]. Zhang et al (2022) screened diagnostic biomarkers and identified the landscape of immune infiltration in DCM (dataset GSE141910 from Geo).…”
Section: Discussionmentioning
confidence: 99%
“…Si (2023) has screened the associated genes and biological pathways of inflammatory dilated cardiomyopathy (DCMi) [ 50 ]. Luo et al (2020) identified novel long non-coding RNA (lncRNA) biomarkers associated with DCM and revealed the potential molecular mechanisms of DCM development using bioinformatics approaches (dataset GSE5406 from GEO) [ 51 ]. Zhang et al (2022) screened diagnostic biomarkers and identified the landscape of immune infiltration in DCM (dataset GSE141910 from Geo).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has revealed that lncRNA Xist acted as powerful and dynamic modifier of cardiac physiological and pathological processes. Cardiac hypertrophy, recognized as a risk predictor of sudden cardiac death, is an adaptive reaction in response to altered stress or injury to maintain cardiac function ( Li Y. et al, 2018 ; Wehbe et al, 2019 ; Luo X. et al, 2020 ). lncRNA Xist ( Sohrabifar, 2020 ) participates in the pathogenesis of complex diseases and also serves as a diagnostic marker.…”
Section: The Role Of Lncrna Xist In Non-cancer Diseasesmentioning
confidence: 99%
“…Camargo A et al [12] established the DCM classi cation model by analyzing the public data sets, and nally identi ed the potential biomarkers and drug targets of DCM. In addition, Luo X et al [13] used bioinformatics approaches to reveal the underlying molecular mechanisms and therapeutic targets of DCM (chip dataset GSE1156). However, the results of these data analysis have not been veri ed and further systematic research needs to be performed.…”
Section: Introductionmentioning
confidence: 99%